The morphology of the intraparietal sulcus in children prenatally exposed to alcohol in a sample of children from the Western Cape, South Africa and its potential relationship with number processing - Greeff, Marlie (Department of Human Biology, 2021)
The intraparietal sulcus (IPS) is a prominent feature in the parietal lobe and extends posteriorly from the postcentral sulcus through the parietal lobe to end in the occipital. It is involved in visuospatial functions and is known to play a critical role in number processing. Fetal alcohol spectrum disorders (FASD) result from prenatal exposure to alcohol and are particularly prevalent in the Western Cape region of South Africa. Arithmetic is a domain of cognitive function that is particularly sensitive to prenatal alcohol exposure, and effects on arithmetic remain significant after controlling for lower IQ. Magnetic resonance imaging (MRI) was used to investigate the morphology of the IPS and whether this morphology had a relation to the number processing abilities of children prenatally exposed to alcohol in a Western Cape community. Participants were 9 to 14-year-old children from the same community in Cape Town, South Africa, who formed part of a study aimed at investigating the effects of prenatal alcohol exposure (PAE) on brain structure and function particularly during number processing. Mothers were interviewed regarding alcohol consumption during pregnancy using a timeline follow-back approach. The first analysis included designing a protocol for manually parcellating the IPS into two regions of interest (ROI): the medial wall (MIPS) and the lateral wall (LIPS) respectively. The neuroimaging program MultiTracer was used for the manual tracing and to calculate the volume of the cortex of both the MIPS and LIPS. The purpose of this first analysis was to examine the effects of PAE on IPS volume and asymmetry using manual tracing, the relation between IPS volume and number processing performance, and potential moderation by PAE of the relation between IPS volume and number processing performance. Results indicated that when comparing the FAS/PFAS (Fetal Alcohol Syndrome/Partial FAS) children to the controls, PAE had an effect on the left LIPS and higher arithmetic scores were associated with larger bilateral MIPS volumes suggesting that the effect of PAE on math may not be moderated by IPS volume. The left LIPS was significantly smaller in FAS/PFAS individuals when compared by FASD diagnosis, and this remained a trend after controlling for potential confounders. In the second analysis, the automated neuroimaging software program FreeSurfer was used to parcellate the IPS. These volumes were then compared with our previously manually traced volumes. Intra-rater reliability testing was statistically significant for consistency and absolute agreement indicating good retraceability of the designed protocol for manual tracing. Both left and right IPS volumes were significantly larger with the manually traced method compared to automated tracing. The manually traced left IPS yielded stronger results when comparing volumes by diagnostic groups, conversely the automated volumes showed stronger associations with alcohol measures. A possible explanation is that FreeSurfer parcellated the IPS differently to our protocol and does not take into account the extensive variability of the morphology of the sulcus. BrainVoyager QX, another neuroimaging software program was used in the third analysis when looking at the BOLD fMRI data of the participants. For this analysis, the manually traced MIPS and LIPS were subdivided into five ROI's for the left and right hemispheres respectively: (1) the superior MIPS, (2) the medial branch of the MIPS, (3) the inferior MIPS, (4) the superior LIPS, and (5) the inferior LIPS. The percent signal change were calculated for each participant for the proximity judgement (PJ) tasks they performed inside the scanner. Associations of the percent signal change of the ROI's of the PAE children with absolute alcohol per occasion (oz) were all significant even after controlling for IQ except the left inferior LIPS, supporting what is found in the literature. The current findings, in agreement with previous studies, demonstrate that PAE is associated with both structural and functional changes in the brain. While the morphology of the IPS may not moderate the effects of PAE on arithmetic function, some cortical volumes within the IPS were sensitive to PAE. Moreover, altered activation of the IPS in the performance of magnitude comparison tasks was strongly associated with PAE. The IPS is an extremely variable structure whose anatomy is often misunderstood, which emphasises the importance of anatomical knowledge for imaging studies. Future research will refine the protocol for manual tracing of the IPS, which may lead to greater understanding of the functions of the different areas. It is to be hoped that these findings will give more insight into understanding the functioning of children and adults with FASDs and contribute to more effective therapeutic interventions for these individuals.